Climate vulnerability and government resource mobilization in developing countries - Pierre Christian Tsopmo; Suzie Imelda Foudjo; Michelle Josée Ekila Elanga (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
There is substantial empirical literature on the impact of climate vulnerability on economic outcomes in developing countries. However, this literature is still weak on the impact of climate vulnerability on tax revenue mobilization. To enrich the existing literature, this paper aims to investigate the effects of climate vulnerability on government revenue mobilization in a sample of 84 developing countries over the period 1995-2019. To achieve this objective, we use the pooled ordinary least square and fixed-effects ordinary least square regressor techniques as developed by Driscoll and Kraay (1998). We obtain three main results. First, climate vulnerability hampers government revenue mobilization in developing countries. Indeed, a variation of 1 per cent in the level of climate vulnerability induces a decrease in government revenues of 0.63 points. Second, climate vulnerability has different impacts on each type of government tax revenue. Regarding the subcomponents of tax revenue (direct and indirect tax), the results confirm the harmful effect of climate vulnerability on all these subcomponents. Furthermore, it appears that direct taxes are the most compromised in terms of magnitude. Third, this effect does not change when climate vulnerability is disaggregated (exposure, sensitivity, and adaptive capacity). However, the climate sensitivity index has a significantly greater effect than the other two. Finally, by applying quantile regression and the two-step system generalized method of moments to control, respectively, distributional heterogeneity and the potential endogenous problem, we also find that climate vulnerability hampers government revenue mobilization in developing countries. These results suggest recommendations relative to the implementation of measures meant to improve the resilience of people to climate change and natural disasters.
Keywords: E62; H20; O13; Q54; 330; climate vulnerability; developing countries; government revenue mobilization; natural disasters